Ablation of ORMDL3 impairs adipose tissue thermogenesis and insulin sensitivity by increasing ceramide generation - Yu Song; Wenying Zan; Liping Qin; Shuang Han; Lili Ye; Molin Wang; Baichun Jiang; Pan Fang; Qiji Liu; Changshun Shao; Yaoqin Gong; Peishan Li (Elsevier, 2022)
Objective: Genome-wide association studies identified ORMDL3 as an obesity-related gene, and its expression was negatively correlated with body mass index. However, the precise biological roles of ORMDL3 in obesity and lipid metabolism remain uncharacterized. Here, we investigate the function of ORMDL3 in adipose tissue thermogenesis and high fat diet (HFD)-induced insulin resistance. Methods: Ormdl3-deficient (Ormdl3−/−) mice were employed to delineate the function of ORMDL3 in brown adipose tissue (BAT) thermogenesis and white adipose tissue (WAT) browning. Glucose and lipid homeostasis in Ormdl3−/− mice fed a HFD were assessed. The lipid composition in adipose tissue was evaluated by mass spectrometry. Primary adipocytes in culture were used to determine the mechanism by which ORMDL3 regulates white adipose browning. Results: BAT thermogenesis and WAT browning were significantly impaired in Ormdl3−/− mice upon cold exposure or administration with the β3 adrenergic agonist. In addition, compared to WT mice, Ormdl3−/− mice displayed increased weight gain and insulin resistance in response to HFD. The induction of uncoupling protein 1 (UCP1), a marker of thermogenesis, was attenuated in primary adipocytes derived from Ormdl3−/− mice. Importantly, ceramide levels were elevated in the adipose tissue of Ormdl3−/− mice. In addition, the reduction in thermogenesis and increase in body weight caused by Ormdl3 deficiency could be rescued by inhibiting the production of ceramides. Conclusion: Our findings suggest that ORMDL3 contributes to the regulation of BAT thermogenesis, WAT browning, and insulin resistance.